Fostering place-based coalitions between social movements and science for sustainable urban environments: A case of embedded agency. (November 2020) - Ramirez, Matias; Estevez, Javier Hernando Garcia; Goyeneche, Oscar Yandy Romero; Rodriguez, Claudia E Obando
The objective of this paper is to contribute to an important debate concerning the interaction between place-based social movements and the science, technology and innovation system. Our central proposition is that place-based social movements can facilitate unique local heterogeneous alliances with key actors of the science and technology system. A process of bricolage can emerge from these alliances whereby social movements are supported by the technical knowledge of the science community, and in turn, the priorities of the scientists are influenced by the agendas of the social movements, leading to new forms of knowledge production. We build on this to argue that these place-based engagements can create significant agency towards changes in socio-technical and socio-ecological systems in urban environments, especially in societies where regulatory oversight is weaker and social movements in areas that overlap science, technology and innovation are a common expression of civil society demand for change. Our argument is developed through a study of a social movement in defence of an urban wetland in Bogota.